Egoism, Utility, and Friendship in Plato’s Lysis - Deretic, Irina (Revista Archai, 2023)
Many scholars consider that Socrates in the Lysis holds that friendship and love are egoistic and utility-based. In this paper, I will argue against those readings of Plato’s Lysis. I will analyze how Socrates treats utility and egoism in the many different kinds of friendship he discusses in the dialogue, from parental love, like-to-like, and unlike-to-unlike relationships, to the accounts of friendship rooted in the human relation to the good and the ways in which we can belong with some other human beings. The upshot of my paper is twofold. I endeavor to prove that some of these relationships, as Plato’s Socrates discusses them, are not egoistic and that Plato represents and valorizes a particular type of friendship having to do with philosophy and philosophical way of life, which is for the sake of another.